Water-soluble films and packaging
By adjusting the crystallinity index of water-soluble PVA films using FT-IR with diamond and germanium prisms, the film adhesion and solubility issues are resolved, ensuring rapid dissolution and mechanical strength, particularly in cold water.
Patent Information
- Application Number
- JP2023092920
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-12-28
- Filing Date
- 2023-06-06
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2039-12-27
AI Technical Summary
Water-soluble PVA films used for packaging drugs face issues with adhesion between films due to reduced crystallinity, requiring strict humidity control and increasing storage and transportation costs, while increasing crystallinity reduces water solubility, especially in cold regions.
Adjusting the crystallinity index of the film surface layer to specific ranges using FT-IR measurements with diamond and germanium prisms, ensuring Fd1 ≦ 0.55, Fd1/Fg1 < 1, Fd2 ≦ 0.65, and Fd2/Fg2 < 1, while maintaining mechanical strength and solubility.
The solution effectively suppresses film adhesion and maintains excellent water solubility, ensuring quick dissolution and mechanical integrity, particularly in cold water, while minimizing curling and handling issues.
Smart Images

Figure 0007600309000002 
Figure 0007600309000003 
Figure 0007600309000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a water-soluble film containing a water-soluble polyvinyl alcohol resin, which is suitable for use in packaging various medicines, and a package using the same. [Background technology]
[0002] Water-soluble films have traditionally been used widely for packaging materials for various chemicals such as detergents and pesticides, as well as seeds, and the demand for these films is expanding due to their ease of use.
[0003] As a water-soluble film for such applications, a PVA film containing polyvinyl alcohol (hereinafter sometimes referred to as "PVA") as a main component is widely used. In order to improve various physical properties of this water-soluble film, various techniques have been proposed. For example, water-soluble films with improved water solubility have been proposed by blending various additives such as plasticizers or using modified PVA (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-078166 A Summary of the Invention [Problem to be solved by the invention]
[0005] The water-soluble film disclosed in Patent Document 1 has its crystallinity reduced and its water solubility increased by adjusting the amount of added plasticizers, etc., or by using modified PVA. However, if the crystallinity of a water-soluble film is simply reduced, the PVA film will easily absorb moisture and will easily cause adhesion between films. Therefore, very strict humidity control is required during storage of a film roll in which a PVA film is wound around a cylindrical core, or a package containing a drug, which can result in a decrease in handleability and an increase in storage and transportation costs.
[0006] One solution to this problem is to increase the crystallinity of the film, but this method can reduce the film's water solubility, especially in cold water for use in cold climates.
[0007] An object of the present invention is to provide a water-soluble film that can suppress the occurrence of adhesion between films while maintaining excellent water solubility, and a package using the same. [Means for solving the problem]
[0008] As a result of extensive research, the inventors have found that the above-mentioned object can be achieved by adjusting the crystallinity index of the surface layer of a water-soluble film containing a polyvinyl alcohol-based resin within a specific range. Based on this finding, the inventors have conducted further research and have completed the present invention.
[0009] The present invention relates to the following [1] to
[11] . [1] A water-soluble film containing a polyvinyl alcohol-based resin, The polyvinyl alcohol resin has a degree of saponification of 64 to 95 mol %, The time required for complete dissolution of the water-soluble film when immersed in deionized water at 10° C. is within 90 seconds; When the first surface of the water-soluble film is subjected to FT-IR measurement by the ATR method, the crystallinity index calculated using a diamond prism is Fd1 and the crystallinity index calculated using a germanium prism is Fg1, A water-soluble film, wherein Fd1 and Fg1 satisfy the following formulae: Fd1 ≦ 0.55 (1) Fd1 / Fg1 < 1 (2) [2] The water-soluble film according to the above [1], wherein Fd1 satisfies the following formula: Fd1 ≧ 0.25 (3) [3] The water-soluble film according to the above [1] or [2], wherein Fd1 and Fg1 satisfy the following formula: Fd1 / Fg1 ≧ 0.5 (4) [4] When the FT-IR measurement by the ATR method is performed on a second surface of the water-soluble film opposite to the first surface, the crystallinity index calculated using the diamond prism is Fd2 and the crystallinity index calculated using the germanium prism is Fg2, The water-soluble film according to any one of the above [1] to [3], wherein Fd2 and Fg2 satisfy the following formula: Fd2 ≦ 0.65 (5) Fd2 / Fg2 < 1 (6) [5] The water-soluble film according to [4] above, wherein Fd2 satisfies the following formula: Fd2 ≧ 0.25 (7) [6] The water-soluble film according to [4] or [5] above, wherein Fd2 and Fg2 satisfy the following formula: Fd2 / Fg2 ≧ 0.5 (8) [7] The water-soluble film according to any one of the above [4] to [6], wherein Fd1 and Fd2 satisfy the following formula: |Fd1-Fd2| ≦ 0.07 (9) [8] The water-soluble film according to any one of the above [4] to [7], wherein Fg1 and Fg2 satisfy the following formula: |Fg1-Fg2| ≦ 0.07 (10) Effect of the Invention
[0010] According to the present invention, it is possible to provide a water-soluble film that can suppress the occurrence of adhesion between films while maintaining excellent water solubility, and a package using the same. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is a diagram showing an example of an infrared absorption spectrum of a film. [Diagram 2] FIG. 1 is a schematic diagram showing an ATR method in infrared absorption spectrum measurement. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be specifically described below.
[0013] The water-soluble film of the present invention (hereinafter sometimes referred to as "PVA film") contains a polyvinyl alcohol-based resin. It is important that the crystallinity index calculated by analyzing one surface (also referred to as "first surface") of the PVA film with FT-IR (Fourier transform infrared spectroscopy) satisfies the following formula. That is, when the crystallinity index obtained by the measurement value of FT-IR analysis using a diamond prism for one surface of the PVA film is Fd1 and the crystallinity index obtained by the measurement value of FT-IR analysis using a germanium prism is Fg1, the following formula is satisfied. Fd1 ≦ 0.65 (1) Fd1 / Fg1 < 1 (2) When Fd1 exceeds 0.65, the PVA film is insufficiently water-soluble.Fd1 is preferably 0.60 or less, more preferably 0.55 or less, even more preferably 0.5 or less, and particularly preferably 0.45 or less. When Fd1 / Fg1 is 1 or more, it is not possible to achieve both excellent water solubility of the PVA film and suppression of the occurrence of sticking between films. Fd1 / Fg1 is preferably 0.98 or less, more preferably 0.96 or less, even more preferably 0.94 or less, even more preferably 0.92 or less, and particularly preferably 0.9 or less.
[0014] <FT-IR Measurement> The water-soluble film of the present invention contains a polyvinyl alcohol-based resin (PVA). When measuring the infrared absorption spectrum of the water-soluble film, an absorption peak is usually observed at 1140 cm -1 . This peak is generally referred to as the crystallization band of the PVA film and is one of the peaks derived from the stretching vibration of the carbon bond (C-C). It is known that this peak is observed with enhanced intensity when the phase of the vibration becomes aligned due to crystallization of the polymer molecular chains in the PVA film. The higher the crystallinity of the PVA film, the relatively higher the peak intensity. In the present invention, the intensity ratio between the absorption peak intensity at 1140 cm -1 and the absorption peak intensity observed at 1425 cm -1 derived from the bending vibration of methylene (-CH2-), which is the PVA main chain and is not dependent on the crystallinity, is calculated to obtain the crystallinity index of the film. Specifically, as shown in FIG. 1, the baseline of the infrared absorption spectrum at 1140 cm -1 and 1425 cm -1 is drawn. The heights from the baseline to the peak tops at 1140 cm -1 and 1425 cm -1 are taken as the absorption peak intensities respectively. The value obtained by dividing the absorption peak intensity at 1140 cm -1 by the peak intensity at 1425 cm -1 is taken as the crystallinity index. It is well known that the value of the crystallinity index thus obtained is proportional to the crystallinity of the PVA film (for example, N.A. Peppas, Macromol. Chem., Vol. 178, 595 (1977), JP-A-6-138321). Since the value of this crystallinity index varies slightly depending on the moisture absorption amount of the film, in the present invention, after storing the film for 24 hours in an environment of temperature: 24.0 °C, relative humidity: 45.0%RH, FT-IR measurement is performed in this environment.
[0015] In the present invention, the FT-IR measurement is performed by the ATR method (attenuated total reflection method). As shown in FIG. 2, the ATR method is a type of reflection-type IR analysis method in which a film is placed in close contact with an objective lens called an ATR prism, infrared light is irradiated obliquely onto the film from within the ATR prism, and the spectrum of the reflected light is measured. This method is characterized by obtaining a sharper spectrum with less noise than the normal reflection-type IR analysis method. In this measurement method, the infrared light is not only reflected by the surface of the film, but also the infrared light that has penetrated slightly from the prism side into the film side is reflected, making it possible to obtain information about the film surface and surface layer. If the penetration depth of this infrared light is d, its value is expressed by the following formula. d= λ / 2Πn1× 1 / {sin 2 θ-(n2 / n1) 2} 0.5 (11) Here, n1 is the refractive index of the prism, n2 is the refractive index of the film, λ is the wavelength of the infrared light, and θ is the angle of incidence of the infrared light. As is clear from this formula, by using prisms with different refractive indices, it is possible to obtain infrared absorption spectra with reflections of different penetration depths.
[0016] In the present invention, as shown in Fig. 2, diamond with n1 of 2.4 and germanium with n1 of 4.0 are used as prisms. When these prisms are used, the incident angle is 45° and the wave number is 1140 cm -1 When calculating the penetration depth of infrared light into the film surface in this case, the refractive index of PVA is 1.5, so it is about 2 μm for diamond prisms and about 0.5 μm for germanium prisms. In other words, the crystallinity index when diamond prisms are used corresponds to the crystallinity up to a relatively deep inside of the film, whereas the crystallinity index when germanium prisms are used corresponds to the crystallinity near the surface of the film, in the very surface layer. In the above formula (2), Fd1 / Fg1 being smaller than 1 indicates that the degree of crystallinity is higher near the surface of the film, in the extreme surface layer, than the degree of crystallinity relatively deep inside the film. It is presumed that by precisely controlling the degree of crystallinity between the interior and extreme surface layers of the film in this manner, one of the characteristics of the film of the present invention is able to achieve both suppression of adhesion between films and excellent water solubility.
[0017] In the present invention, the lower limit of Fd1 is not necessarily limited, but from the viewpoint of the mechanical strength of the film, it is preferable that the following formula (3) is satisfied. Fd1 ≧ 0.25 (3) If Fd1 is less than 0.25, the crystallinity of the water-soluble PVA film is low near the center in the thickness direction, and the mechanical strength of the film may be weakened. In addition, the package using the film may be torn, and the encapsulated medicine may leak. The lower limit of Fd1 is more preferably 0.3 or more, even more preferably 0.35 or more, and particularly preferably 0.4 or more. By satisfying the above range of Fd1, the mechanical strength of the film can be maintained at a suitable level.
[0018] In the present invention, the lower limit of Fd1 / Fg1 is not necessarily limited, but from the viewpoint of solubility in low-temperature water, it is preferable that the following formula (4) is satisfied. Fd1 / Fg1 ≧ 0.5 (4) When Fd1 / Fg1 is less than 0.5, the crystallinity of the extreme surface layer of the water-soluble PVA film is significantly higher than that of the relatively deep inside of the film, and the solubility in low-temperature water may decrease. The lower limit of Fd1 / Fg1 is more preferably 0.6 or more, even more preferably 0.7 or more, and particularly preferably 0.8 or more.
[0019] In the present invention, when the crystallinity index Fd2 determined from the measured value of FT-IR analysis using a diamond prism is defined as Fd2 for one surface (also referred to as the "first surface") of the PVA film and the opposing surface (also referred to as the "second surface") are defined as the crystallinity index Fg2 determined from the measured value of FT-IR analysis using a germanium prism, it is preferable that the following formula is satisfied. Fd2 ≦ 0.65 (5) Fd2 / Fg2 < 1 (6) By setting Fd2 in the above range not only on one surface but also on the other surface facing the one surface, the water solubility of the PVA film can be more optimally maintained. Fd2 is preferably 0.60 or less, more preferably 0.55 or less, even more preferably 0.5 or less, and particularly preferably 0.45 or less. From the viewpoints of excellent water solubility of the PVA film and further suppression of the occurrence of sticking between films, Fd2 / Fg2 is preferably less than 1. Fd2 / Fg2 is preferably 0.98 or less, more preferably 0.96 or less, even more preferably 0.94 or less, even more preferably 0.92 or less, and particularly preferably 0.9 or less. By setting the crystallinity index within the above range not only on one surface of the PVA film but also on the other surface, i.e., on both surfaces of the film, the excellent water solubility of the PVA film can be further improved and adhesion between films can be further suppressed.
[0020] In the present invention, the lower limit of Fd2 is not necessarily limited, but from the viewpoint of the mechanical strength of the film, it is preferable that the following formula (7) is satisfied. Fd2 ≧ 0.25 (7) If Fd2 is less than 0.25, the crystallinity of the other surface of the water-soluble PVA film near the center in the thickness direction is further reduced, and the mechanical strength of the film is further weakened. In addition, the package using the film may be torn, causing leakage of the encapsulated drug or the like. The lower limit of Fd2 is more preferably 0.3 or more, even more preferably 0.35 or more, and particularly preferably 0.4 or more. By satisfying the above range of Fd2, the mechanical strength of the film can be further maintained.
[0021] In the present invention, the lower limit of Fd2 / Fg2 is not necessarily limited, but from the viewpoint of solubility in low-temperature water, it is preferable that the following formula (8) is satisfied. Fd2 / Fg2 ≧ 0.5 (8) If Fd2 / Fg2 is less than 0.5, the crystallinity of the extreme surface layer of the other surface of the water-soluble PVA film is significantly higher than that of the relatively deep inside of the film, and the solubility in low-temperature water may be further reduced. The lower limit of Fd2 / Fg2 is more preferably 0.6 or more, even more preferably 0.7 or more, and particularly preferably 0.8 or more.
[0022] In the present invention, the relationship between Fd1 and Fd2 is not necessarily limited, but from the viewpoint of being able to suppress the occurrence of curling of the film, it is preferable that the following formula (9) is satisfied. |Fd1-Fd2| ≦ 0.07 (9) That is, in the present invention, it is preferable that the difference in crystallinity index between one surface and the other surface of the film is not too large. If the difference in crystallinity index between one surface and the other surface of the film exceeds 0.07, problems such as curling of the film are likely to occur during secondary processing of the film. The difference in crystallinity index between one surface and the other surface of the film is more preferably 0.06 or less, even more preferably 0.05 or less, and particularly preferably 0.04 or less.
[0023] In the present invention, the relationship between Fg1 and Fg2 is not necessarily limited, but from the viewpoint of being able to suppress the occurrence of curling of the film, it is preferable that the following formula (10) is satisfied. |Fg1-Fg2| ≦ 0.07 (10) That is, in the present invention, it is preferable that the difference in crystallinity index between one surface and the other surface of the film is not too large. If the difference in crystallinity index between one surface and the other surface of the film exceeds 0.07, problems such as curling of the film are likely to occur during secondary processing of the film. The difference in crystallinity index between one surface and the other surface of the film is more preferably 0.06 or less, even more preferably 0.05 or less, and particularly preferably 0.04 or less.
[0024] In the present invention, it is important to control the crystallinity index of the water-soluble PVA film within the above range at the very surface layer and in the thickness direction from the very surface layer. Since the crystal structure of the PVA film is affected by various factors in the film composition and manufacturing process, examples of the method for controlling the crystallinity index include a method for adjusting the type of polyvinyl alcohol resin (saponification degree, modification amount, blend ratio of unmodified PVA / modified PVA, etc.), a method for adjusting the amount of plasticizer added, a method for adjusting the film manufacturing conditions (surface temperature of the roll support, heat treatment conditions, etc.), or a method for adjusting by a combination of these.
[0025] <Polyvinyl alcohol resin> The water-soluble film of the present invention contains a polyvinyl alcohol resin (PVA). As the PVA, a polymer produced by saponifying a vinyl ester polymer obtained by polymerizing a vinyl ester monomer can be used. Examples of vinyl ester monomers include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, vinyl versatate, etc. Among these, vinyl acetate is preferred as the vinyl ester monomer.
[0026] The vinyl ester polymer is preferably a polymer obtained by using only one or more vinyl ester monomers as a monomer, more preferably a polymer obtained by using only one vinyl ester monomer as a monomer. The vinyl ester polymer may be a copolymer of one or more vinyl ester monomers and another monomer copolymerizable therewith.
[0027] Examples of other monomers include ethylene; olefins having 3 to 30 carbon atoms, such as propylene, 1-butene, and isobutene; acrylic acid or a salt thereof; acrylic acid esters, such as methyl acrylate, ethyl acrylate, n-propyl acrylate, i-propyl acrylate, n-butyl acrylate, i-butyl acrylate, t-butyl acrylate, 2-ethylhexyl acrylate, dodecyl acrylate, and octadecyl acrylate; methacrylic acid or a salt thereof; methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, methacrylic acid, and the like. Methacrylic acid esters such as i-propyl acrylate, n-butyl methacrylate, i-butyl methacrylate, t-butyl methacrylate, 2-ethylhexyl methacrylate, dodecyl methacrylate, and octadecyl methacrylate; acrylamides such as acrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetone acrylamide, acrylamidopropanesulfonic acid or a salt thereof, acrylamidopropyldimethylamine or a salt thereof, and N-methylolacrylamide or a derivative thereof; methacrylamide derivatives such as methacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, methacrylamidepropanesulfonic acid or a salt thereof, methacrylamidepropyldimethylamine or a salt thereof, N-methylolmethacrylamide or a derivative thereof; N-vinylamides such as N-vinylformamide, N-vinylacetamide, N-vinylpyrrolidone; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, i-propyl vinyl ether, n-butyl vinyl ether, i-butyl vinyl ether, t-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether; vinyl cyanides such as acrylonitrile and methacrylonitrile; vinyl halides such as vinyl chloride, vinylidene chloride, vinyl fluoride, and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; maleic acid or a salt, ester, or acid anhydride thereof; itaconic acid or a salt, ester, or acid anhydride thereof; vinyl silyl compounds such as vinyltrimethoxysilane; and isopropenyl acetate. The vinyl ester polymer may have structural units derived from one or more of these other monomers.
[0028] Generally, the crystallization of PVA tends to proceed more slowly as the proportion of structural units derived from other monomers in the vinyl ester polymer increases, so the crystallinity index of the PVA film can be adjusted by copolymerizing these other monomers in an appropriate amount. The proportion of structural units derived from other monomers in the vinyl ester polymer is not necessarily limited, but is preferably 15 mol % or less, and more preferably 5 mol % or less, based on the number of moles of all structural units constituting the vinyl ester polymer.
[0029] Generally, the higher the degree of polymerization, the less likely the crystallization of PVA is to proceed. Therefore, in the present invention, the degree of polymerization of PVA is not particularly limited, but is preferably in the following range. That is, the lower limit of the degree of polymerization is preferably 200 or more, more preferably 300 or more, and even more preferably 500 or more, from the viewpoint of suppressing excessive crystallization and ensuring sufficient mechanical strength of the PVA film. On the other hand, the upper limit of the degree of polymerization is preferably 8,000 or less, more preferably 5,000 or less, and even more preferably 3,000 or less, from the viewpoint of moderate crystallization progression and increasing the productivity of PVA and the productivity of the PVA film.
[0030] Here, the degree of polymerization means the average degree of polymerization measured in accordance with the description of JIS K 6726-1994. In this specification, the degree of polymerization is calculated from the intrinsic viscosity [η] (unit: deciliter / g) measured in water at 30° C. after resaponifying and purifying the PVA, according to the following formula (12). Degree of polymerization Po = ([η]×10 4 / 8.29) (1 / 0.62) (12)
[0031] Generally, the crystallization of PVA tends to proceed more easily as the saponification degree is higher. Therefore, the saponification degree of PVA is not necessarily limited in the present invention, but is preferably 64 to 95 mol%. By adjusting the saponification degree of PVA to this range, the crystallization of the PVA film can be moderately advanced, and it is easy to achieve both good water solubility and suppression of adhesion between films. The lower limit of the saponification degree is more preferably 70 mol% or more, and even more preferably 75 mol% or more. On the other hand, the upper limit of the saponification degree is more preferably 94 mol% or less, and even more preferably 93 mol% or less.
[0032] Here, the degree of saponification of PVA refers to the ratio (mol %) of the number of moles of vinyl alcohol units to the total number of moles of structural units (typically vinyl ester monomer units) that can be converted to vinyl alcohol units by saponification and vinyl alcohol units. The degree of saponification of PVA can be measured in accordance with the description of JIS K 6726-1994.
[0033] The PVA film may contain one type of PVA alone, or may contain two or more types of PVA differing from each other in the degree of polymerization, degree of saponification, degree of modification, and the like.
[0034] The upper limit of the PVA content in the PVA film is preferably 100% by mass or less, while the lower limit of the PVA content is preferably 50% by mass or more, more preferably 80% by mass or more, and even more preferably 85% by mass or more.
[0035] <Plasticizer> PVA films that do not contain plasticizers are generally hard films, and therefore tend to cause problems such as breakage during film formation and secondary processing. In addition, the feel of the film is poor, so it is preferable for PVA films to contain a plasticizer. By including a plasticizer, the PVA film can be given the same flexibility as other plastic films.
[0036] Examples of the plasticizer include polyhydric alcohols such as ethylene glycol, glycerin, diglycerin, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, trimethylolpropane, and sorbitol. These plasticizers may be used alone or in combination of two or more. Among these, ethylene glycol or glycerin is preferred as the plasticizer, and glycerin is more preferred, because it is difficult to bleed out onto the surface of the PVA film.
[0037] In general, the addition of a moderate amount of plasticizer to PVA promotes crystallization. This is presumably because the addition of plasticizer makes the PVA molecules more mobile, making it easier for them to assume an energetically more stable crystalline or constrained amorphous structure. On the other hand, PVA films containing excess plasticizer tend to inhibit the progress of crystallization. This is presumably because the amount of plasticizer that interacts with the hydroxyl groups of the PVA molecules increases, weakening the interactions between the PVA molecules. The lower limit of the plasticizer content in the PVA film is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by mass of PVA. On the other hand, the upper limit of the content of the plasticizer is preferably 70 parts by mass or less, more preferably 50 parts by mass or less, and even more preferably 40 parts by mass or less, relative to 100 parts by mass of PVA. When the content of the plasticizer is within the above range, it becomes easy to control the crystallinity index of the PVA film, and in addition, the effect of improving mechanical properties such as impact strength can be sufficiently obtained. In addition, it is possible to suitably prevent or suppress the PVA film from becoming too flexible, which reduces the handling properties, or causes problems such as bleeding out to the surface.
[0038] <Starch / Water-soluble polymer> The PVA film may contain a water-soluble polymer other than starch and / or PVA. By containing a water-soluble polymer other than starch and / or PVA, it is possible to impart mechanical strength to the PVA film, improve the moisture resistance of the PVA film during handling, or adjust the speed at which the PVA film softens due to absorption of water during dissolution.
[0039] Examples of starches include natural starches such as corn starch, potato starch, sweet potato starch, wheat starch, rice starch, tapioca starch, and sago starch; and processed starches that have been subjected to etherification, esterification, oxidation, etc., with processed starches being particularly preferred.
[0040] The content of starch in the PVA film is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, based on 100 parts by mass of PVA. When the content of starch is within the above range, deterioration of the processability of the PVA film can be prevented or suppressed.
[0041] Examples of water-soluble polymers other than PVA include dextrin, gelatin, glue, casein, shellac, gum arabic, polyacrylic acid amide, sodium polyacrylate, polyvinyl methyl ether, a copolymer of methyl vinyl ether and maleic anhydride, a copolymer of vinyl acetate and itaconic acid, polyvinylpyrrolidone, cellulose, acetyl cellulose, acetyl butyl cellulose, carboxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, and sodium alginate.
[0042] The content of the water-soluble polymer other than PVA in the PVA film is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, based on 100 parts by mass of PVA. When the content of the water-soluble polymer other than PVA is within the above range, the water solubility of the PVA film can be sufficiently increased.
[0043] <Surfactant> The PVA film preferably contains a surfactant, which can improve the handling properties of the PVA film and the peelability of the PVA film from a film-forming device during production. The surfactant is not particularly limited, and for example, anionic surfactants, nonionic surfactants, etc. can be used.
[0044] Examples of anionic surfactants include carboxylic acid surfactants such as potassium laurate; sulfate ester surfactants such as octyl sulfate; and sulfonic acid surfactants such as dodecylbenzenesulfonate.
[0045] Examples of nonionic surfactants include alkyl ether type surfactants such as polyoxyethylene lauryl ether and polyoxyethylene oleyl ether; alkyl phenyl ether type surfactants such as polyoxyethylene octylphenyl ether; alkyl ester type surfactants such as polyoxyethylene laurate; alkyl amine type surfactants such as polyoxyethylene lauryl amino ether; alkyl amide type surfactants such as polyoxyethylene lauric acid amide; polypropylene glycol ether type surfactants such as polyoxyethylene polyoxypropylene ether; alkanolamide type surfactants such as lauric acid diethanolamide and oleic acid diethanolamide; and allyl phenyl ether type surfactants such as polyoxyalkylene allyl phenyl ether.
[0046] Such surfactants may be used alone or in combination of two or more. As the surfactant, nonionic surfactants are preferred because they have an excellent effect of reducing surface abnormalities during the formation of a PVA film, alkanolamide surfactants are more preferred, and dialkanolamides (e.g., diethanolamides) of aliphatic carboxylic acids (e.g., saturated or unsaturated aliphatic carboxylic acids having 8 to 30 carbon atoms) are even more preferred.
[0047] The lower limit of the surfactant content in the PVA film is preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, and even more preferably 0.05 parts by mass or more, relative to 100 parts by mass of PVA. On the other hand, the upper limit of the surfactant content is preferably 10 parts by mass or less, more preferably 1 part by mass or less, even more preferably 0.5 parts by mass or less, and particularly preferably 0.3 parts by mass or less, relative to 100 parts by mass of PVA. When the surfactant content is within the above range, the peelability of the PVA film from the film-forming device during production is improved, and problems such as the occurrence of sticking between PVA films (hereinafter sometimes referred to as "blocking") are unlikely to occur. In addition, problems such as bleeding out of the surfactant onto the surface of the PVA film and deterioration of the appearance of the PVA film due to aggregation of the surfactant are unlikely to occur.
[0048] <Other ingredients> The PVA film may contain components such as plasticizers, starch, water-soluble polymers other than PVA, and surfactants, as well as moisture, antioxidants, UV absorbers, lubricants, crosslinking agents, colorants, fillers, preservatives, antifungal agents, and other polymer compounds, as long as the effects of the present invention are not impaired. The proportion of the total mass of PVA, plasticizer, starch, water-soluble polymer other than PVA, and surfactant to the total mass of the PVA film is preferably 60 to 100 mass%, more preferably 80 to 100 mass%, and even more preferably 90 to 100 mass%.
[0049] <Water-soluble film> The PVA film of the present invention is not particularly limited in the time required for complete dissolution when immersed in deionized water at 10°C, but the following range is preferable. That is, the upper limit of the complete dissolution time is preferably within 150 seconds, more preferably within 90 seconds, even more preferably within 60 seconds, and particularly preferably within 45 seconds. A PVA film having an upper limit of the complete dissolution time in the above range is preferably used as a packaging film (packaging material) for medicines and the like, since dissolution is completed relatively quickly. On the other hand, the lower limit of the complete dissolution time is preferably 5 seconds or more, more preferably 10 seconds or more, even more preferably 15 seconds or more, and particularly preferably 20 seconds or more. A PVA film having a lower limit of the complete dissolution time in the above range is less likely to cause problems such as blocking between PVA films due to absorption of moisture in the atmosphere and a decrease in mechanical strength.
[0050] The time required for a PVA film to completely dissolve when immersed in deionized water at 10° C. can be measured as follows. <1> The PVA film is placed in a thermohygrostat adjusted to 20°C and 65% RH for 16 hours or more to condition the humidity. <2> A rectangular sample 40 mm long x 35 mm wide is cut out from the conditioned PVA film, and then the sample is clamped and fixed between two 50 mm x 50 mm plastic plates with a rectangular window (hole) 35 mm long x 23 mm wide, so that the length of the sample is parallel to the length of the window and the sample is positioned approximately in the center of the window width. <3> Put 300 mL of deionized water into a 500 mL beaker and adjust the water temperature to 10° C. while stirring with a magnetic stirrer equipped with a 3 cm long bar at a rotation speed of 280 rpm. <4> the above <2> The sample fixed to a plastic plate in is immersed in deionized water in a beaker, taking care not to let it come into contact with the bar of a rotating magnetic stirrer. <5> The time (seconds) from immersion in deionized water until the sample pieces dispersed in the deionized water completely disappear is measured.
[0051] The thickness of the PVA film is not particularly limited, but is preferably in the following range. That is, the upper limit of the thickness is preferably 200 μm or less, more preferably 150 μm or less, even more preferably 100 μm or less, and particularly preferably 50 μm or less. On the other hand, the lower limit of the thickness is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and particularly preferably 20 μm or more. Since the thickness in the above range is not too large, it is possible to suitably prevent the secondary processability of the PVA film from deteriorating, while it is not too small, so that sufficient mechanical strength can be ensured for the PVA film. The thickness of the PVA film can be determined by measuring the thickness at any 10 points (for example, any 10 points on a line drawn in the longitudinal direction of the PVA film) and averaging the measured thicknesses.
[0052] <Method of manufacturing water-soluble film> The method for producing the water-soluble film (PVA film) of the present invention is not particularly limited, and any of the following methods can be used, for example. Examples of such methods include a method in which a film-forming stock solution obtained by adding a solvent, additives, etc. to PVA to make it homogenous is formed by casting film-forming method, wet film-forming method (discharging into a poor solvent), dry-wet film-forming method, gel film-forming method (a method in which the film-forming stock solution is cooled to gel, and then the solvent is extracted and removed), or a combination of these methods, and a melt extrusion film-forming method or inflation molding method in which a film-forming stock solution obtained using an extruder or the like is extruded from a T-die or the like to form a film. Among these, the casting film-forming method and the melt extrusion film-forming method are preferred as methods for producing PVA films. By using these methods, a homogenous PVA film can be obtained with good productivity. Hereinafter, the case where a PVA film is produced by a casting film-forming method or a melt extrusion film-forming method will be described.
[0053] When the PVA film is produced by the casting film-forming method or the melt extrusion film-forming method, first, a film-forming solution containing PVA, a solvent, and, if necessary, an additive such as a plasticizer is prepared. When the film-forming solution contains an additive, the ratio of the additive to the PVA in the film-forming solution is substantially equal to the ratio of the additive to the PVA in the PVA film described above. Next, the film-forming solution is dripped (supplied) in the form of a film onto a rotating support such as a metal roll or a metal belt. This forms a liquid coating of the film-forming solution on the support. The liquid coating is heated on the support to remove the solvent, and is solidified into a film. Examples of methods for heating the liquid coating include a method of heating the support itself to a high temperature using a heat medium, and a method of blowing hot air onto the surface of the liquid coating opposite the surface in contact with the support. The solidified long film (PVA film) is peeled off from the support, dried using a drying roll or a drying oven as necessary, and further heat-treated as necessary, and then wound up into a roll.
[0054] During the drying process (solvent removal process) of the liquid coating that has been poured onto the support, and the subsequent drying process of the PVA film, PVA crystallizes while it is heated. The rate of crystallization at this time is affected by the proportion of structural units derived from other monomers, the degree of polymerization, the degree of saponification, and the amount of plasticizer, as well as the moisture content in the PVA, temperature, and draw (tensile elongation in the flow direction). The draw is presumed to be the effect of oriented crystallization caused by the tension of the PVA molecular chains. Usually, drying of PVA film proceeds by volatilization of volatile matter from the open film surface that is not in contact with the support or drying rolls. Therefore, during the drying process, a concentration distribution of volatile matter such as water occurs in the thickness direction of the film, and a distribution of crystallinity index occurs in the thickness direction depending on the temperature and drawing conditions at each time. This distribution of crystallinity index can be adjusted by the support temperature, contact time with the support, hot air temperature and amount, drying roll and drying oven temperature, etc. Therefore, by appropriately adjusting each of the above factors, the water-soluble PVA film of the present invention can be obtained.
[0055] The volatile content of the film-forming solution (the concentration of volatile components such as solvents removed by volatilization or evaporation during film formation) is preferably 50 to 90% by mass, more preferably 55 to 80% by mass. When the volatile content is within the above range, the viscosity of the film-forming solution can be adjusted to a suitable range, improving the film-forming properties of the PVA film (liquid coating) and making it easier to obtain a PVA film with a uniform thickness. In addition, since the volatile content of the film-forming solution is appropriate, the crystallization of PVA on the support proceeds appropriately, making it easier to adjust the crystallinity index and its distribution.
[0056] In this specification, the "volatile content of the film-forming solution" refers to a value calculated by the following formula. Volatile content of film-forming solution (mass%) ={(Wa-Wb) / Wa}×100 (13) In the formula, Wa represents the mass (g) of the film-forming solution, and Wb represents the mass (g) of the film-forming solution Wa (g) after drying for 16 hours in an electric dryer at 105°C.
[0057] The method for preparing the film-forming solution is not particularly limited, and examples thereof include a method in which PVA and additives such as a plasticizer and a surfactant are dissolved in a dissolution tank or the like, and a method in which PVA in a water-containing state is melt-kneaded together with additives such as a plasticizer and a surfactant using a single-screw or twin-screw extruder.
[0058] The film-forming solution generally passes through the die lip of a die such as a T-die and is cast in the form of a film onto a support such as a metal roll or a metal belt. As described above, on the support, the solvent evaporates from the surface of the cast film-like solution that is not in contact with the support (hereinafter, sometimes referred to as the free surface), while it does not substantially evaporate from the surface that is in contact with the support (hereinafter, sometimes referred to as the touch surface), resulting in a distribution in which the solvent concentration is low on the free surface side and high on the touch surface side in the thickness direction of the film. Therefore, the solidification of PVA also proceeds from the free surface first. In parallel with the solidification of PVA, crystallization of PVA also proceeds. Crystallization of PVA is difficult when the solvent concentration is too high or too low, and although it depends on the primary structure of the PVA molecule, it is easy to proceed when the volatile content in the dribble PVA film is in the range of 20 to 60 mass%. The higher the temperature, the faster the crystallization speed, but the higher the temperature, the faster the solvent evaporates. Therefore, in order to efficiently proceed with crystallization of the extreme surface of the PVA film, it is important to control the temperature of the support, the contact time with the support, and the like, as well as the temperature of the atmosphere near the free surface and the vapor pressure of the solvent. Since the PVA film of the present invention has a high degree of crystallinity in the extreme surface layer compared to the degree of crystallinity in the relatively deep interior of the film, it is only necessary to select conditions that allow crystallization of the extreme surface layer of the film to proceed while suppressing crystallization in the relatively deep interior of the film. For example, conditions for slow drying, such as lowering the drying temperature, can be adopted in the early stages of drying when the volatile fraction of the extreme surface layer is decreasing, thereby increasing the moisture content of the extreme surface layer while crystallization proceeds, and conditions for rapid drying at a relatively high temperature can be adopted in the middle to late stages of drying, when crystallization proceeds relatively deep inside the film, thereby allowing crystallization to proceed.
[0059] The surface temperature of the support onto which the film-forming solution is applied is preferably 50 to 110° C., more preferably 60 to 100° C., and even more preferably 65 to 95° C. When the surface temperature is within the above range, drying of the liquid coating and crystallization of the outermost surface layer of the film proceed at an appropriate speed, making it easier to obtain the PVA film of the present invention.
[0060] While the liquid coating is heated on the support, hot air may be blown uniformly onto the entire area of the non-contact side of the liquid coating at a speed of 1 to 10 m / sec. The temperature of the hot air blown onto the non-contact side is preferably 50 to 150°C, more preferably 70 to 120°C. The humidity of the hot air is preferably in the range of 20 to 90% RH, more preferably 30 to 80% RH, and even more preferably 40 to 80% RH. When the temperature and humidity of the hot air blown onto the non-contact side are within the above ranges, the PVA film of the present invention can be easily obtained.
[0061] The PVA film is dried (solvent removed) on the support preferably until the volatile content is 5 to 50% by mass, and then peeled off from the support and further dried as necessary. The drying method is not particularly limited, and examples thereof include a method of passing the mixture through a drying oven and a method of contacting the mixture with a drying roll. When drying the PVA film using multiple drying rolls, it is preferable to alternately contact one surface of the PVA film with the drying rolls. This makes it possible to control the difference in the crystallinity index of PVA on both sides of the PVA film. In this case, the number of drying rolls is preferably 3 or more, more preferably 4 or more, and even more preferably 5 to 30.
[0062] The temperature of the drying oven or drying roll is preferably 40 to 110°C. The upper limit of the temperature of the drying oven or drying roll is more preferably 100°C or less, even more preferably 90°C or less, and particularly preferably 85°C or less. On the other hand, the lower limit of the temperature of the drying oven or drying roll is more preferably 45°C or more, and even more preferably 50°C or more. By setting the temperature of the drying oven or drying roll within the above upper and lower limits, it becomes easier to obtain a PVA film having the effects of the present invention. If it is outside the above upper and lower limits, Fd1 and Fd2 tend to be large, and it may be difficult to obtain the film of the present invention.
[0063] The dried PVA film can be further subjected to heat treatment as necessary, which allows the mechanical strength, water solubility, and other properties of the PVA film to be adjusted.
[0064] The heat treatment temperature is preferably 60 to 135°C. The upper limit of the heat treatment temperature is more preferably 130°C or less. By setting the heat treatment temperature within the above range, it becomes easier to obtain a PVA film having the effects of the present invention. If the heat treatment temperature exceeds the above range, the difference in crystallinity index between the very surface layer part and the relatively deep inside of the PVA film becomes too small, which may make it difficult to obtain the PVA film of the present invention.
[0065] The PVA film produced in this manner may be further subjected to moisture conditioning treatment, cutting of both ends (edges) of the film, etc., as necessary, and then wound into a roll on a cylindrical core and packaged in a moisture-proof package to complete the product.
[0066] The volatile content of the PVA film finally obtained by a series of treatments is not necessarily limited, but is preferably 1 to 5 mass %, more preferably 2 to 4 mass %.
[0067] <Application> The water-soluble film (PVA film) of the present invention has an excellent balance between water solubility and resistance to adhesion between films, and can be suitably used in various film applications in which general water-soluble films are used. Examples of such film applications include medicinal packaging films, hydraulic transfer base films, embroidery substrate films, release films for artificial marble molding, seed packaging films, and films for waste collection bags. Among these, the water-soluble film of the present invention is preferably applied to medicinal packaging films, since the effects of the present invention are more pronounced.
[0068] When the water-soluble film of the present invention is applied to a film for packaging medicines, the types of medicines include, for example, agricultural chemicals, detergents (including bleaching agents), and disinfectants. The physical properties of the drug are not particularly limited, and it may be acidic, neutral, or alkaline. The agent may also contain a boron-containing compound or a halogen-containing compound.
[0069] The drug may be in any form, such as powder, block, gel or liquid. The packaging form is not particularly limited, and a unit packaging form in which the drug is packaged (preferably sealed) in a unit amount is preferred. The package of the present invention can be obtained by applying the water-soluble film of the present invention to a drug packaging film to package a drug. In other words, the package of the present invention includes a packaging material (capsule) made of the water-soluble film of the present invention and a drug encapsulated in the packaging material.
Example
[0070] The present invention will be specifically described below with reference to examples and the like. However, the present invention is not limited to the following examples. The evaluation items and methods of the water-soluble PVA film are as follows.
[0071] <Dissolution time of PVA film> Using the above method, the dissolution time (seconds) when the PVA film was immersed in deionized water at 10 °C was measured.
[0072] <Calculation of crystallization index by FT-IR measurement> As described above, since the value of the crystallinity index varies slightly depending on the moisture absorption amount of the film, in the present invention, the film was stored for 24 hours in an environment of temperature: 24.0 °C, relative humidity: 45.0%RH, and measured with an FT-IR installed in a room of the same environment. The measurement was performed on both sides of the film under the following conditions.
[0073] Measuring device: NICOLET is 10 (manufactured by Thermo Fisher) Measurement conditions: One-time reflection ATR method, incident angle 45° Resolution: 4.0 cm -1 Number of integrations: 32 times Measurement temperature: 24.0 °C (environmental temperature) Measurement humidity: 45.0%RH (environmental relative humidity) Prism: Diamond or germanium
[0074] The IR spectra of both sides of the PVA film were measured by FT-IR, and the crystallinity index was calculated by the above method.
[0075] <Difficulty of adhesion between water solubility and PVA film> The water-soluble film was cut into a size of 3 cm x 20 cm, rolled into a cylinder with an inner diameter of about 1 cm around the short side, and then both ends were cut off. This produced a small water-soluble film roll with an inner diameter of 1 cm and width of 1 cm. Using a double clip with a mouth width of 15 mm (manufactured by Kokuyo Co., Ltd., product name Scel-bo), the vicinity of the central axis of the obtained roll was clamped so that the direction of the clamping part of the clip coincided with the axial direction of the roll, and the roll was stored for 16 hours under conditions of 60°C-90% RH. The film roll after storage was unwound, and the state of adhesion between the contact surfaces at the ends was evaluated.
[0076] Evaluation criteria: ◯: There was no sticking between the contacting surfaces at the ends, and the water-soluble film could be unwound without resistance. △: Resistance was felt when unwinding, but the water-soluble film could be unwound by applying force. ×: The contact surfaces at the ends were stuck together, and the water-soluble film could not be unwound.
[0077] <Curl> A water-soluble PVA film was cut into a size of 20 cm x 20 cm, and stored for 24 hours in an environment of temperature: 24.0°C and relative humidity: 45.0%RH while hanging by a clip. The film was then placed on a horizontal surface, and the curling that occurred at the film edge was evaluated according to the following criteria. Note that the surface of the film in contact with the horizontal surface was the outer surface of the curled film if the film curled.
[0078] Evaluation criteria: ◯: No curl was observed at any edge, or the angle between the horizontal plane and the edge of the film was visually small, at 45° or less. △: Slight curl was observed at one of the edges. Slight curl here means that the angle between the horizontal plane and the edge of the film was more than 45° and less than 180° when visually observed. An angle of 180° or more between the horizontal plane and the edge of the film means that the edge of the film came into contact with the PVA film in the center due to curling. ×: At any one of the edges, the angle between the plane and the edge of the film exceeded 180°, i.e., the edge of the film was curled into a cylindrical shape.
[0079] <Example 1> A film-forming solution was prepared by mixing 100 parts by mass of PVA (saponification degree 88 mol%, viscosity average polymerization degree 1700) obtained by saponifying polyvinyl acetate, 10 parts by mass of glycerin as a plasticizer, 0.1 parts by mass of lauric acid diethanolamide as a surfactant, and water. The volatile content of the film-forming solution was 68% by mass. Next, the film-forming solution was discharged from the T-die onto a first drying roll (surface temperature 80°C) in the form of a film to form a liquid film on the first drying roll. On the first drying roll, hot air at 85°C was blown onto the entire surface of the liquid film that was not in contact with the first drying roll at a speed of 5 m / sec to dry it. This produced a PVA film. Next, the dried PVA film (dried to a moisture content of 32% by mass) was peeled off from the first drying roll, and one side of the PVA film was alternately brought into contact with each drying roll to dry, and then wound into a roll on a cylindrical core. The surface temperature of the rolls after the second drying roll was set to about 75° C. The obtained PVA film had a thickness of 35 μm and a width of 1200 mm. The time it took for the PVA film to completely dissolve at 10°C was measured. The IR spectrum of the PVA film was then measured by FT-IR to calculate the crystallinity index, and the water solubility, resistance to adhesion between PVA films, and curling of the PVA film were evaluated. The results are shown in Table 1.
[0080] <Example 2> A PVA film was obtained in the same manner as in Example 1, except that the PVA used in preparing the film-forming solution was changed to acrylamide-2-methylpropanesulfonate sodium (AMPS) modified PVA (saponification degree 88 mol%, polymerization degree 1700, AMPS modification amount 2 mol%). The complete dissolution time at 10°C, crystallinity index, water solubility, resistance to sticking between PVA films, and curling of the PVA film were evaluated for the obtained PVA film. The results are shown in Table 1.
[0081] <Example 3> A PVA film was obtained in the same manner as in Example 1, except that the PVA used in preparing the film-forming solution was changed to a maleic acid monomethyl ester (MMM) modified PVA (saponification degree 90 mol%, polymerization degree 1700, MMM modification amount 5 mol%). The complete dissolution time at 10°C, crystallinity index, water solubility, sticking resistance between PVA films, and curling of the PVA film were evaluated for the obtained PVA film. The results are shown in Table 1.
[0082] <Example 4> A PVA film was obtained in the same manner as in Example 3, except that after drying, only one side of the PVA film was heat-treated by contacting it with a metal roll having a surface temperature of 120° C. for 30 seconds. The complete dissolution time at 10° C., crystallinity index, water solubility, resistance to sticking between PVA films, and curling of the PVA film were evaluated for the obtained PVA film. The results are shown in Table 1.
[0083] <Comparative Example 1> A PVA film was obtained in the same manner as in Example 3, except that after drying, the PVA film was heat-treated in a hot air oven at 130°C for 90 seconds. The time to complete dissolution at 10°C, the crystallinity index, water solubility, resistance to adhesion between PVA films, and curling of the PVA film were evaluated for the obtained PVA film. The results are shown in Table 1.
[0084] <Comparative Example 2> A PVA film was obtained in the same manner as in Example 1, except that the surface temperature of the first drying roll was changed to 115°C, the temperature of the hot air blown onto the surface of the liquid coating not in contact with the first drying roll was changed to 120°C, and the temperature of the second drying roll and onward was changed to 65°C. The complete dissolution time at 10°C, the crystallinity index, water solubility, the resistance to sticking between PVA films, and the curling of the PVA film were evaluated for the obtained PVA film. The results are shown in Table 1.
[0085] The evaluation results of the obtained water-soluble film are shown in Table 1.
[0086] [Table 1]
Claims
1. A water-soluble film containing a polyvinyl alcohol-based resin, The polyvinyl alcohol resin has a degree of saponification of 64 to 95 mol %, The time required for complete dissolution of the water-soluble film when immersed in deionized water at 10° C. is within 90 seconds; When FT-IR measurement by the ATR method is performed on the first surface of the water-soluble film, the crystallinity index calculated using a diamond prism is Fd1 and the crystallinity index calculated using a germanium prism is Fg1, A water-soluble film, wherein Fd1 and Fg1 satisfy the following formulas. Fd1 ≦ 0.55 (1) Fd1 / Fg1 < 1 (2)
2. The water-soluble film according to claim 1 , wherein Fd1 satisfies the following formula: Fd1 ≧ 0.25 (3)
3. 3. The water-soluble film according to claim 1, wherein Fd1 and Fg1 satisfy the following formula: Fd1 / Fg1 ≧ 0.5 (4)
4. When the FT-IR measurement by the ATR method is performed on a second surface of the water-soluble film opposite to the first surface, the crystallinity index calculated using the diamond prism is Fd2 and the crystallinity index calculated using the germanium prism is Fg2, The water-soluble film according to any one of claims 1 to 3, wherein Fd2 and Fg2 satisfy the following formula: Fd2≦0.65 (5) Fd2 / Fg2 < 1 (6)
5. The water-soluble film according to claim 4, wherein Fd2 satisfies the following formula: Fd2 ≧ 0.25 (7)
6. 6. The water-soluble film according to claim 4, wherein Fd2 and Fg2 satisfy the following formula: Fd2 / Fg2 ≧ 0.5 (8)
7. The water-soluble film according to any one of claims 4 to 6, wherein Fd1 and Fd2 satisfy the following formula: |Fd1-Fd2| ≦ 0.07 (9)
8. The water-soluble film according to any one of claims 4 to 7, wherein Fg1 and Fg2 satisfy the following formula: |Fg1-Fg2| ≦ 0.07 (10)
Citation Information
Patent Citations
Method of manufacturing polarizing film
JP2014016649A
Method for producing polyvinyl alcohol film
JP2016222834A
Water-soluble film and medicine package
JP2017078166A
Polyvinyl alcohol-based polymer film and manufacturing process therefor
WO2014050696A1
Polyvinyl alcohol polymer film and method for producing same
WO2016084836A1
